Captain Underpants and the terrifying return of Tippy Tinkletrousers - Pilkey, Dav (London : Scholastic, 2012)
After being sent to jail for the rest of their lives, George and Harold are taken on a trip back in time by Tippy Tinkletrousers back to their Kindergarten days where they must deal with their bully without the help of Captain Underpants.
O
b
b